The Effect of Using Cube and Block Nets on the Results of Visually Impaired Learners - Ika Fitriyah Tyastuti; Bachtiar Syaiful Bachri; Utari Dewi (Jurnal Amal Pendidikan, 2023)
Mathematics is a subject that is currently considered to have a high level of difficulty compared to other subjects for students. Especially for blind students. Visually impaired learners experience limited senses of vision that can affect understanding and reasoning about the material of Cube and Beam Spaces taught by educators. In this study, the Cube and Beam Nets media was applied which aims to facilitate students in understanding the material of cube and beam nets by assembling cube and beam nets so that they can form cubes and beams. Research was conducted to determine the learning outcomes of students before and after the use of media. In this study, the method used was quantitative method. The research instrument used in this research is a written test with braille letters combined with embossed paper to bring up the nets of cubes and blocks in the test instrument sheet. The type of research used in this research is exsperiment with the research design used, namely one group pre-test post-test with research subjects 6 students. The average result of the pre-test obtained is 43.3, while the average value of the post-test obtained is 85. The data obtained was then analyzed using non-parametric statistical analysis with Zscore = 2.20 greater than Ztable = 1.96 with a value of n = 6 (α = 5% so that H0 is rejected and Ha is accepted). If H0 is rejected and Ha  is accepted, then in the study there is a significant influence before the use of media and after the use of 3-dimensional media nets of cubes and beams.